Effect of thickness of porous polysulfone membranes on removal of ferum ions / Norin Zamiah Kassim Shaari, Nabilla Mohamed Zaimy and Nurul Aida Sulaiman - Kassim Shaari, Norin Zamiah; Mohamed Zaimy, Nabilla; Sulaiman, Nurul Aida (Universiti Teknologi MARA Shah Alam, 2018)
Membrane separation has been widely used in the removal of heavy metal from wastewater. Chemical precipitation, ion exchange, and adsorption are the examples of conventional treatment that have significance disadvantages which are incomplete removal and high energy consumption, thus lead to disposal of toxic sludge. In this research, the wastewater from electroplating industry containing high concentration of ferum ion was treated by using an integrated complexation method through a thin film composite membrane. The composite comprises of polysulfone as support layer with either polymer blend of PVA/chitosan and hybrid membrane respectively as the top layer. Treatment process was conducted at pH 7, room temperature, and pressure of 12 bar. The thickness of polysulfone was varied at 60 μm and 90 μm. Results showed that the treated wastewater contained ferum concentration below than the acceptable range and the composite membrane with hybrid membrane as thin layer with polysulfone at 90 μm thickness yield the best performance.